THE ROLE OF CREDIT UNION BETANG ASI FOR FAMILY BUSINESSES IN PALANGKARAYA, CENTRAL KALIMANTAN - I Wayan Ruspendi Junaedi; I Wayan Damayana; Dermawan Waruwu; Suresh Kumar (International Journal of Family Business Practices, 2022)
This study aims at finding the role of Credit Union (CU) Betang Asi, a financial institution under the OJK, in developing the family businesses in Palangkaraya, Central Kalimantan. The study method used was a qualitative study method, by conducting observations, interviews with owners and managers of family businesses, and documentation. The findings are that CU has contributed a lot to the welfare of family businesses in Palangkara, Central Kalimantan. The family businesses have developed to the maximum so that the sales turnover is quite attractive. Further, CU considers the Character, Capacity, Capital, Condition, and Collateral characteristics as the most important aspect of lending money to family businesses. They also provide training and assistance to be able to improve the business of management and marketing management and the use of technology. Hence, they can increase sales of the business and inspire the community to become entrepreneurs to improve the welfare of the business.